Public policies for indigenous families in Misiones - Enriz, Noelia (2011)
The aim of this paper is to address public policies targeted to indigenous families in the Misiones province. This intervention can be divided into three periods. The first one began in the mid 70s and was characterized by a very intensive public policy in two specific areas of the province. These policies included interventions in a wide variety of fields, for example education, health, housing, production, etc. The second period began around 2004, when a unique indigenous protest took place in the provincial capital demanding changes in welfare policies. From this point, a third period of policies emerged, marked by access to universal policies. We will approach this issue analyzing documentary sources and discourses of participants involved in the programs.